A hybrid discrete particle swarm algorithm for solving the fixed-spectrum frequency assignment problem. (14th December 2009) - Benameur, L.; Alami, J.; El Imrani, A.
In this paper, the problem of the fixed-spectrum frequency assignment, where the objective is to minimise the cost due to the interference arising in a solution, is studied and solved using a discrete particle swarm optimisation, which is refined by a deterministic local search heuristic. Computational results, obtained for eight well-known benchmarks problem, confirm the effectiveness of discrete particle swarm optimisation.